PENGARUH E-BANKING TERHADAP KINERJA KEUANGAN (STUDI KASUS PADA PERBANKAN DENGAN MARKET CAP TERATAS DI INDONESIA) - Purnamasari, Natasya Yunior; Fadli, Faishal (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The use of technology in the banking sector is currently growing rapidly with the presence of E-banking. E-banking may affect financial performance and can increase banking profits. The purpose of this study is to determine the effect of E-banking on the financial performance of banks with the top market cap. ROA is used as the dependent variable to represent financial performance. The independent variables used are ATM, M-banking, DPK and BOPO by adding bank size as a control variable. The samples used are BBCA, BBRI, BMRI, BBNI and MEGA. The type of data used is secondary data with panel data regression analysis of the annual financial report data of each bank from 2015-2022. The results of this study are ATM, M-banking and BOPO have a significant effect on ROA while DPK has no significant effect on ROA. Simultaneously, ATM, M-banking, DPK, BOPO and Bank Size variables have a significant effect on ROA. Therefore, the implication of this research is that banks focus on improving and developing E-banking in order to increase bank profits which will improve the bank's financial performance.